Lethal weapon 2 [videorecording (DVD)] - Donner, Richard; Gibson, Mel; Glover, Danny; Pesci, Joe (Warner Home Video, 1997)
Riggs and Murtaugh must guard a free-wheeling witness in a comedy of car chases, gun battles, under-water escapes, even the destruction of a chic hillside house.